2008
DOI: 10.1002/anie.200800339
|View full text |Cite
|
Sign up to set email alerts
|

Osmium(II) CNN Pincer Complexes as Efficient Catalysts for Both Asymmetric Transfer and H2 Hydrogenation of Ketones

Abstract: Catalytic asymmetric hydrogenation (HY) and transfer hydrogenation (TH) of carbonyl compounds are usually performed with Ru, Rh, and Ir complexes, [1] and much less attention has been devoted to other transition-metal basedsystems. Although osmium complexes have occasionally been employed in the HY [2] and TH [3] of carbonyl compounds, we have recently shown that [OsCl 2 P 2 (Pyme)][4a] [P 2 = diphosphane; Pyme = 1-(pyridin-2-yl)methanamine)] complexes are extremely active catalysts in the TH of ketones, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 140 publications
(48 citation statements)
references
References 27 publications
1
47
0
Order By: Relevance
“…[1e] Recently, the Ru and Os phosphane complexes cis-[MCl 2 (PP)A C H T U N G T R E N N U N G (ampy)] (M = Ru, [13] Os; [14] PP = diphosphane, ampy = 2-(aminomethyl)pyridine) were found to be highly efficient catalysts for the (asymmetric) transfer hydrogenation and hydrogenation of ketones. Furthermore, the related pincer complexes [MClA C H T U N G T R E N N U N G (CNN)(PP)] (M = Ru, [15] Os [16] ), prepared by using 6-(4'-methylphenyl)-2-pyridylmethylamine (HCNN), catalyze the reduction of carbonyl compounds with high productivity when using 0.05-0.001 mol % of catalyst and a high rate (turnover frequency (TOF) up to Abstract: The ruthenium and osmium complexes…”
Section: A C H T U N G T R E N N U N G (=Chph)a C H T U N G T R E N Nmentioning
confidence: 99%
“…[1e] Recently, the Ru and Os phosphane complexes cis-[MCl 2 (PP)A C H T U N G T R E N N U N G (ampy)] (M = Ru, [13] Os; [14] PP = diphosphane, ampy = 2-(aminomethyl)pyridine) were found to be highly efficient catalysts for the (asymmetric) transfer hydrogenation and hydrogenation of ketones. Furthermore, the related pincer complexes [MClA C H T U N G T R E N N U N G (CNN)(PP)] (M = Ru, [15] Os [16] ), prepared by using 6-(4'-methylphenyl)-2-pyridylmethylamine (HCNN), catalyze the reduction of carbonyl compounds with high productivity when using 0.05-0.001 mol % of catalyst and a high rate (turnover frequency (TOF) up to Abstract: The ruthenium and osmium complexes…”
Section: A C H T U N G T R E N N U N G (=Chph)a C H T U N G T R E N Nmentioning
confidence: 99%
“…In this context, introduction of a chiral moiety as part of the ligand framework to create transition-metal catalysts for asymmetric reactions has been investigated. Recently, several highly reactive Ru and Os complexes with chiral CNN-type ligands [2] and Fe and Co complexes with chiral bis(pyridylimino)isoindole ligands [3] were reported as active chiral catalysts.During our investigation of transition-metal catalysts with chiral meridional NCN ligands, we reported the bis(oxazolinyl)phenyl (phebox) ligand as one of a larger family of ligands including bis(oxazolinyl)pyridine (pybox).[4] Although the meridional geometry of the phebox ligand is similar to that of the pybox ligand, the metal complex with the phebox ligand possesses a metal-carbon s bond that may induce different reactivities. We anticipated that the simple change from a benzene substituent to a pyridine ring as the ligand backbone would lead to a change in the catalytic performance of the complex.…”
mentioning
confidence: 99%
“…These have been demonstrated to be powerful catalysts for the enantioselective reduction of ketones and imines. Recently, Baratta and co-authors [11] found that 2-(aminomethyl) pyridine (ampy) accelerated the transfer hydrogenation (TH) of ketones [12][13][14] in Ru(II) and Os(II) complex catalysts. Very recently, Morris group [15,16] reported that chiral NNPP ligands and their iron(II) complexes were effective in the ATH of ketones under mild conditions, representing a rare case of using inexpensive iron as the active metal.…”
Section: Introductionmentioning
confidence: 99%